PENGARUH E-SERVICE QUALITY DAN KEAMANAN TRANSAKSI TERHADAP PERCEIVED VALUE CUSTOMER BISNIS E-COMMERCE: STUDI KASUS PADA PT. TOKOPEDIA - Giasinta Panatra; Tony Sitinjak (Jurnal Manajemen, 2020)
This study aims to measure how the relationship and influence from e-service quality and securetransactions to customer’s perceived value toward online shopping applications on Tokopedia.Independent variable used in this study is e-service quality and secure transactions, while the dependentvariable is customer’s perceived value.Collection technique used is to use primary data in the form of interviews and questionnaires.Mechanical sampling is done by using judgmental or purposive sampling. Testing the hypothesis throughSPSS System on 152 respondents. Respondents in majority are female, young adults in 23-28 years old,employees, S1 and have been used Tokopedia.The results showed that the proven positive effect on the e- service quality toward customer’s perceivedvalue significantly. And secure transaction also give a positif effect toward to customer’s perceived valuesignificantly. This study provides in- depth understanding of the relationship between e-service quality,secure transactions, and perceived value.